Partisipasi Masyarakat Pada Pembayaran Pajak Bumi dan Bangunan di Desa Kasimbar Palapi Kecamatan Kasimbar Kabupaten Parigi Moutong - hajria, Hajria; Nuraisyah; Dandan Haryono (JPS: Journal of Publicness Studies, 2024)
This study aims to find out how the community participates in paying land and building taxes in Kasimbar Palapi Village. This study uses descriptive research methods and qualitative analysis using systematic methods in making observations, collecting data, analyzing information and reporting the results. The types of data used in this research are primary and secondary which are divided into interviews, documentation and information from informants. Based on the results of the study, it can be seen that community participation in paying land and building taxes in Kasimbar Palapi Village, Kasimbar District, Parigi Moutong Regency can be said to be quite good. by looking at several factors that affect participation, among others, communication that has been established positively, positive attitude changes, the awareness they have is still lacking, the enthusiasm given by the community is not great so it can be said to be less positive, and the sense of responsibility that arises within all parties is still lacking, with these five points not being fulfilled we can see that the payment of land and building tax in Kasimbar Palapi Village is still relatively lacking